2006
DOI: 10.1603/0022-2585(2006)043[0309:eotott]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on the Transmission of West Nile Virus by <I>Culex tarsalis</I> (Diptera: Culicidae)

Abstract: Culex tarsalis Coquillett females were infected with the NY99 strain of West Nile virus (family Flaviviridae, genus Flavivirus, WNV) and then incubated under constant temperatures of 10-30 degrees C. At selected time intervals, transmission was attempted using an in vitro capillary tube assay. The median time from imbibing an infectious bloodmeal until infected females transmitted WNV (median extrinsic incubation period, EIP50) was estimated by probit analysis. By regressing the EIP rate (inverse of EIP50) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
300
3
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(317 citation statements)
references
References 31 publications
13
300
3
1
Order By: Relevance
“…Previous laboratory and field studies identified Cx. tarsalis as one of the most important vectors in western United States, [22][23][24][25] including North Dakota. 26 Our current investigations confirm this conclusion, but we also documented Ae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous laboratory and field studies identified Cx. tarsalis as one of the most important vectors in western United States, [22][23][24][25] including North Dakota. 26 Our current investigations confirm this conclusion, but we also documented Ae.…”
Section: Resultsmentioning
confidence: 99%
“…36 It was relatively abundant in North Dakota from the end of June through the end of August, had a relatively high IR during the summer, is efficient in transmitting this virus horizontally, 22,24,25,37 and is relatively efficient in transmitting this virus vertically. 24,38,39 Culex tarsalis was collected during the weeks of June 2 to October 6, similar to collections made in Grand Forks, North Dakota, 26 Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Increased temperatures cause an upsurge in the growth rates of vector populations, decrease the interval between blood meals, shorten the incubation time from infection to infectiousness in mosquitoes, accelerate the virus evolution rate and increase viral transmission efficiency to birds [22,23,30,32,35,36].…”
Section: (A) Temperaturementioning
confidence: 99%
“…Since the virus's emergence, WNV has been a frequent cause of viral encephalitis in equines and humans within the United States (Azad andThomas 2004, Petersen et al 2012), and infection has been recorded naturally in $326 avian species, spanning across most native North American avian orders (Marra et al 2004, Centers for Disease Control [CDC] 2009). Despite widespread impact on both avian and human communities, gaps remain in our understanding of WNV transmission dynamics, particularly how the virus persists in temperate climates when cold temperatures preclude viral replication and diminish vector blood-feeding activity (Reisen et al 2006b). Overwintering mechanisms are critically important because they determine the prevalence of virus at the termination of winter and thereby may dictate the force of transmission during vernal amplification.…”
mentioning
confidence: 99%
“…Ornithophagic species within the genus Culex are important vectors and responsible for zoonotic WNV transmission among birds (Molaei et al 2006). Culex in California are quiescent or diapause during cold winter months (Nelms et al 2013a,b), and low temperatures hinder WNV replication within the overwintering mosquito hosts (Dohm et al 2002, Reisen et al 2006b). Nevertheless, researchers in New York State documented American Crow (Corvus brachyrhynchos; hereafter "crow") mortality during February and March of 2005 (Dawson et al 2007).…”
mentioning
confidence: 99%